2016
DOI: 10.1186/s40689-016-0016-3
|View full text |Cite
|
Sign up to set email alerts
|

Removal of heavy metal chromium from tannery effluent using ultrafiltration membrane

Abstract: The present study was aimed to fabricate a novel ultrafiltration membrane using cellulose acetate, nanochitosan, and polyethylene glycol of ratio 1:2:2 by phase inversion method. Analytical techniques such as Fourier transform infrared spectroscopy (FTIR), X-ray diffractometer (XRD), and scanning electron microscopy (SEM) have been employed to characterize the prepared membrane. FTIR and XRD results revealed the formation of blended membrane with increased amorphous nature. SEM studies exhibited the rough surf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(10 citation statements)
references
References 62 publications
1
9
0
Order By: Relevance
“…As mentioned above, the -COOH and -OH groups on the GO and oxidized-MWCNT surface can induce negative charges on the membrane surface, which causes electrostatic repulsion of the ions resulting in increased rejection of the As. In addition to the previous results, Vinodhini et al [82] observed that CA membranes modified with PEG and nanochitosan were also very effective for Cr(VI) removal (95%). This result may also be related to the positive charge of the membrane due to the incorporation of chitosan nanoparticles in its matrix, which would improve its adsorption capacity.…”
Section: Heavy Metals Removalsupporting
confidence: 49%
“…As mentioned above, the -COOH and -OH groups on the GO and oxidized-MWCNT surface can induce negative charges on the membrane surface, which causes electrostatic repulsion of the ions resulting in increased rejection of the As. In addition to the previous results, Vinodhini et al [82] observed that CA membranes modified with PEG and nanochitosan were also very effective for Cr(VI) removal (95%). This result may also be related to the positive charge of the membrane due to the incorporation of chitosan nanoparticles in its matrix, which would improve its adsorption capacity.…”
Section: Heavy Metals Removalsupporting
confidence: 49%
“…Zhang et al (1999) satisfactorily removed Cd 2+ and Sr 2+ ions via adsorption on cellulose/alginic acid (RC-AlC) ion-exchange membrane. Vinodhini and Sudha (2016) fabricated a novel ultrafiltration membrane prepared by phase inversion method using cellulose acetate, nano chitosan, and polyethylene glycol. The membrane was used for toxic hexavalent chromium removal from tannery effluent.…”
Section: Polymeric Membranes For Membrane Adsorptionmentioning
confidence: 99%
“…Similarly, BOD and COD reduction of 56% and 51% respectively have been observed after an extended contact time. The maximum removal of chromium was noted at neutral pH with a membrane thickness of 0.2mm and 100kPa pressure and industrial application of this has been suggested (58).…”
Section: Tertiary Treatmentmentioning
confidence: 83%